Metode Analisis Diskriminan dalam Pengelompokan Kabupaten/Kota di Provinsi Sulawesi Selatan Berdasarkan Indikator Indeks Pembangunan Manusia - Novi Afryanthi S.; Muhammad Arif Tiro; Ansari Saleh Ahmar (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2020)
Abstract. Discriminant analysis is a method in multivariat statistic analysis that related with object which have separated into the defined group defined and see the accuracy  of the formed group. In this research, clustera analysis is used for the first grouping,  cluster  analysis is a statistical analysis which aims to classify some objects based on the characteristics similarity among the object. Data for this study is HDI (Human Development Index)  of indicator in south sulawesi in 2016. The result of this research are 1st cluster (lower  HDI indicator) which have 21 city/ distric and the 2nd cluster (higher  HDI indicator) which have 3 city/distric as the closeness value between the cluster that formed is 0.902 which shows the closeness between the cluster is high . Furthermore, the discriminant function that have formed explains that if the life expectancy increase, the HDI indicator in city/distric in south sulawesi province will decrease but if school  expectation duration in school , average of duration in school, and parity of pur hasing power is increasing, the HDI indicator in city/distric in aouth sulawesi will also increase.Keywords: Cluster analysis, Discriminant analysis , Human development index indicator.